PENINGKATAN PROSES PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN PENDEKATAN SAINTIFIK BAGI SISWAKELAS IV SDN 07 SUNGAI JARING - -, Gusnilawati (Universitas Negeri Padang, 2014)
The purpose of this research is to describe the planning, Implementing and learning outcome of integrated thematic learning using scientific approach for Grade IVelementary school students.This research used qualitative and quantitative approach. The research type was classroom action research which was done in three cycles. The research subject are 20 grade IV elementary school students at SDN 07 Sungai Jaring. The student learning outcome werw 2,48 at cycle 1, 2,93 at cycle II, anda 3,47 at cycle III. The conclution of this research is the scientific approach can inprove integrated thematic learning process of elementary school students at SDN 07 Sungai Jaring. Kata kunci : Pembelajaran Tematik Terpadu, Pendekatan Saintifik